A methodology for the determination of pollen sources in studies of Patagonian camelid coprolites. (February 2017) - Velázquez, Nadia Jimena; Burry, Lidia Susana; Fugassa, Martín Horacio
Abstract: Pollen studies on Patagonian camelid coprolites (Argentina) focus on palaeodiet analyses and palaeoenvironmental reconstructions. The elucidation of the source of pollen in coprolites is a main issue to interpret what and how past facts happened. The aim of this work is to evaluate the source of the pollen contained in both modern Lama guanicoe feces and camelid coprolites to evaluating the post-depositing contamination. Pellets were separated into outer and inner parts, and pollen extraction was made of each for analysis. As to pollen concentration, differences probably linked to the pollination season were found between both parts of the feces. The presence of certain taxa only in the outer part could be due to postdepositional contamination. Coprolites evidenced more Nothofagus anemophilous pollen concentration in the outer surface of feces and certain taxa were only registered in a single part. A separate pollen analysis of the outer and inner parts of modern feces and coprolites yields information referred to contamination by environmental pollen; thus, the items conforming part of the diet of the vegetation area not consumed by the organisms can be discriminated. Highlights: Pollen source of camelid coprolites and modern feces (Patagonia, Argentina) Comparison between pollen spectra: outer and inner parts of camelid coprolites and modern feces Evidence of post-depositional contamination in feces and coprolites